Improving Arabic Speaking Skills through Role Play Based on Al-Arabiyyah Baina Yadaik Dialogues in a Tahfidz Institution - Nurul Izzah Mujahidah; Muhammad Ridwan; Haeruddin Haeruddin; Andi Agussalim (MASI Mandiri Edukasi, 2026)
This study examines how Arabic-speaking skills in non-formal education, such as tahfidz institutions, can be improved through role-play based on dialogues from the book Al-Arabiyyah Baina Yadaik. The study aims to foster more student-centered, collaborative, and active learning at Rumah Tahfidz Asy-Syifaa Gowa, where the textbook has not yet been used optimally to support speaking practice. A Classroom Action Research (CAR) design using the Kemmis & McTaggart model was employed with 10 students. Data were collected through structured observation using a 1–5 Likert scale of eight speaking aspects (fluency, pronunciation, vocabulary, structure, confidence, interaction, expression, and collaboration), student questionnaires, and documentation. Quantitative descriptive analysis showed that the mean speaking scores increased gradually from 22.6 in the pre-cycle to 31.6 in Cycle I and 35.1 in Cycle II. The percentage of students achieving the “good” category increased from 0% to 100%, with 80% of students scoring ≥32. Student responses were positive, with 90% in the “good” category. These findings suggest that role-play using Al-Arabiyyah Baina Yadaik dialogues was associated with improved Arabic-speaking skills in this classroom context. This approach offers a practical strategy for fostering active speaking practice in similar non-formal Arabic learning settings.